1 - Les fondements de la Socioéconométrie - Thiombiano, Taladidia (Africa Development, 2007)
This article aims to deepen the reflection in my work, Vers une approche en économie politique : la Socioéconométrie [Towards a political economic approach : Socioeconometrics] published in 1997, which discusses the cons- truction of the economy based on economic facts. With regard to the complexity of economic facts, which at the beginning is a social act, the article attempts to show that it is important to understand economic realities through a multidimensional approach. An in-depth examination of the construction of some economic theories and facts that helped those constructions to happen shows the importance of the concept of space and time. Yet, it is not about the classical concept of time and space, but about concepts perceived under the angle of their decline or not within the economy. The combination of space and time helps to better understand economic realities as a systemic totality. The systematisation of economic realities leads to a consideration of economic facts as having some sociological implications, and sociological facts as having some economic inci- dences. Lastly, the reflection then examines t e role of econometrics as a means to deepen and understand economic theories.